1983
DOI: 10.3758/bf03196973
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual processing of text during skimming and rapid sequential reading

Abstract: Potential conceptual processing difficulties associated with abbreviating the duration of eye fixations during reading were explored using a rapid sequential visual presentation (RSVP) paradigm in which each word of a text was briefly presented (for as little as 86 msec) at a fixed location. Question answering and accuracy of summaries associated with RSVP were found to be inferior to performance obtained when subjects skimmed conventionally presented passages.RSVP performance was enhanced by inserting brief p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
1
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 29 publications
5
72
1
1
Order By: Relevance
“…These differences in findings may be accounted for by the fact that in Masson's [1983] study there was no blank window between sentences, whereas in Juola et al's [1982] there was. In Masson's study the beginnings and endings of sentences were only indicated by uppercase letters and periods, respectively.…”
Section: Rapid Serial Visual Presentationcontrasting
confidence: 42%
See 1 more Smart Citation
“…These differences in findings may be accounted for by the fact that in Masson's [1983] study there was no blank window between sentences, whereas in Juola et al's [1982] there was. In Masson's study the beginnings and endings of sentences were only indicated by uppercase letters and periods, respectively.…”
Section: Rapid Serial Visual Presentationcontrasting
confidence: 42%
“…In another study Masson [1983] determined the effect that the duration of the blank window had on reading RSVP text. In this study 32 subjects read RSVP text both with and without a blank window between sentences.…”
Section: Rapid Serial Visual Presentationmentioning
confidence: 99%
“…Comparisons of this task to normal reading have typically revealed that with short sentences, results that are typical of normal reading can be obtained. However, when longer passages are presented, the processing system quickly gets overloaded, and comprehension breaks down (see Masson, 1983). With self-paced reading, text is presented a word or two at a time and readers advance the text by pushing a button.…”
Section: Using Eye Movements To Study Language Processing In Readingmentioning
confidence: 99%
“…To find information efficiently, attention must be focused strictly on the area of text where the information is likely to be located (Guthrie, 1988). When skimming, one easily can miss relevant information that could be picked up by a careful reading (Masson, 1983). This failure to locate relevant information may be due to insufficient attention to, and encoding of, each word.…”
mentioning
confidence: 99%
“…To test this model, they have identified search sequences used by adults when examining documents ranging from airplane schedules (Guthrie, 1988) to textbook chapters (Dreher & Guthrie, 1987. Prior to Dreher and Guthrie (1987), the majority of studies that investigated skimming used documents of only a few paragraphs in length (e.g., Kobasigawa et al, 1988;Masson, 1983). Dreher and Guthrie (1987) adapted the Guthrie and Mosenthal (1987) model to the task of locating information in textbooks.…”
mentioning
confidence: 99%